Evaluating the 35°C wet-bulb temperature adaptability threshold for young, healthy subjects (PSU HEAT Project) - Vecellio, Daniel J.; Wolf, S. Tony; Cottle, Rachel M.; Kenney, W. Larry (Journal of applied physiology (1985), 2022)
This study is the first to use empirical physiological observations to examine the well-publicized theoretical 35°C wet-bulb temperature limit for human to extreme environments. We find that uncompensable heat stress in humid environments occurs in young, healthy adults at wet-bulb temperatures significantly lower than 35°C. In addition, uncompensable heat stress occurs at widely different wet-bulb temperatures as a function of ambient vapor pressure. A wet-bulb temperature of 35°C has been theorized to be the limit to human adaptability to extreme heat, a growing concern in the face of continued and predicted accelerated climate change. Although this theorized threshold is based in physiological principles, it has not been tested using empirical data. This study examined the critical wet-bulb temperature (T wb,crit ) at which heat stress becomes uncompensable in young, healthy adults performing tasks at modest metabolic rates mimicking basic activities of daily life. Across six experimentally determined environmental limits, no subject’s T wb,crit reached the 35°C limit and all means were significantly lower than the theoretical 35°C threshold. Mean T wb,crit values were relatively constant across 36°C –40°C humid environments and averaged 30.55 ± 0.98°C but progressively decreased (higher deviation from 35°C) in hotter, dry ambient environments. T wb,crit was significantly associated with mean skin temperature (and a faster warming rate of the skin) due to larger increases in dry heat gain in the hot-dry environments. As sweat rates did not significantly differ among experimental environments, evaporative cooling was outpaced by dry heat gain in hot-dry conditions, causing larger deviations from the theoretical 35°C adaptability threshold. In summary, a wet-bulb temperature threshold cannot be applied to human adaptability across all climatic conditions and where appropriate (high humidity), that threshold is well below 35°C. NEW & NOTEWORTHY This study is the first to use empirical physiological observations to examine the well-publicized theoretical 35°C wet-bulb temperature limit for human to extreme environments. We find that uncompensable heat stress in humid environments occurs in young, healthy adults at wet-bulb temperatures significantly lower than 35°C. In addition, uncompensable heat stress occurs at widely different wet-bulb temperatures as a function of ambient vapor pressure.